L'attractivité touristique à travers la notion d’attachement : cas de la destination Rabat - Abdellatif Elouali; Hassan Faouzi; Mustapha Kouzer; Noura Ettahir (Études Caribéennes)
This article examines the influence of destination brand image on tourists' post-visit behavior through destination attachment and revisit intention. Through this exploratory, quantitative and qualitative study, the article also proposes to verify the mediating role of attachment in the brand image-tourism attractiveness relationship, using the case of the destination Rabat, capital of Morocco.